2018
DOI: 10.1097/ico.0000000000001422
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Parameters in Patients With Wilson Disease

Abstract: This study indicates that patients with WD have differences in the anterior segment parameters including central corneal thickness, keratometric values, anterior and posterior elevations, horizontal visible iris diameter, and anterior chamber depth when compared with healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition to KFR, the evaluation of anterior segment in WD patients showed differences with healthy population. In a study published by Kara et al, 22 patients with WD (mean age 29 years old) were compared to 22 age-and sex-matched controls [64]. WD patients had significantly higher CCT (p < 0.001), keratometric values (p = 0.011), anterior and posterior corneal elevation (p = 0.029 and p = 0.002, respectively), horizontal visible iris diameter (p = 0.001) and anterior chamber depth (p = 0.01) compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to KFR, the evaluation of anterior segment in WD patients showed differences with healthy population. In a study published by Kara et al, 22 patients with WD (mean age 29 years old) were compared to 22 age-and sex-matched controls [64]. WD patients had significantly higher CCT (p < 0.001), keratometric values (p = 0.011), anterior and posterior corneal elevation (p = 0.029 and p = 0.002, respectively), horizontal visible iris diameter (p = 0.001) and anterior chamber depth (p = 0.01) compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…12 Also 360-degree Scheimpflug imaging is reported to be a useful method in detecting and documenting even minute inflammatory retrocorneal deposits, which may be indicative of upcoming allograft rejection after Descemet membrane endothelial keratoplasty. 13 Anterior segment parameters were recently investigated in WD patients by Kara et al 14 They reported that WD patients had thinner CCT, higher keratometric values and shallower ACDs than normal controls. They also concluded that CCT of the WD patients with KF ring was thinner than the patients without KF ring.…”
Section: Discussionmentioning
confidence: 99%